2021
DOI: 10.3390/cancers13051160
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Extracellular Vesicles in Endocrine Resistant Breast Cancer

Abstract: Breast cancer is the most common solid malignancy diagnosed in females worldwide, and approximately 70% of these tumors express estrogen receptor α (ERα), the main biomarker of endocrine therapy. Unfortunately, despite the use of long-term anti-hormone adjuvant treatment, which has significantly reduced patient mortality, resistance to the endocrine treatments often develops, leading to disease recurrence and limiting clinical benefits. Emerging evidence indicates that extracellular vesicles (EVs), nanosized p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 103 publications
2
8
0
Order By: Relevance
“…Here we have found that some miRNAssuppressors of oestrogen signalling are overexpressed in the exosomes of the tamoxifenresistant cells. Considering the possible involvement of exosomes in the transferring of hormonal resistance [32,92], the role of some of these miRNAs in the progression of acquired resistance was analysed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we have found that some miRNAssuppressors of oestrogen signalling are overexpressed in the exosomes of the tamoxifenresistant cells. Considering the possible involvement of exosomes in the transferring of hormonal resistance [32,92], the role of some of these miRNAs in the progression of acquired resistance was analysed.…”
Section: Discussionmentioning
confidence: 99%
“…As a rule, the development of tamoxifen resistance is caused either by an irreversible block of hormonal signalling (suppression of the activity or synthesis of specific intracellular hormone receptors) or by activation of growth-regulating signalling pathways that bypass hormone-dependent signalling. So, in addition to a receptor depletion, among the main factors promoting hormonal resistance, one can distinguish an imbalance between activator proteins and receptor suppressors, ligand-independent activation of the receptor, stimulation of hormone-independent signalling pathways (primarily tyrosine kinase receptors) and thereby support of tumour growth in the absence of hormones [28][29][30][31][32][33][34][35]. One of the best-known examples of such activation is overexpression of Her2/neu oncogene in breast cancer cells, a member of the tyrosine kinase receptor family that controls cell proliferation in the absence of oestrogens [36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Small EVs are nano-sized membrane-derived vesicles containing a plethora of bioactive molecules (i.e., proteins, nucleic acid, lipids, and metabolites) that reflects the molecular profile of cells of origin. Tumor-derived EVs by transferring their cargo to recipient cells promote a wide range of cellular processes involved in breast cancer progression [ 13 ], extracellular matrix remodeling [ 14 ], epithelial-to-mesenchymal transition [ 15 ], immune evasion [ 16 , 17 , 18 ], endocrine- and target-therapy resistance [ 19 , 20 , 21 , 22 ] and premetastatic niche formation [ 23 , 24 ]. In recent decades, many efforts have been made to decipher the molecular cargo of tumor-derived EVs along with its modification during disease progression or in relation to the different environmental stimuli, in order to identify novel putative biomarkers to improve non-invasive liquid biopsy tools for cancer detection, classification and tailored therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%
“…They are a heterogeneous class and they form mainly from either endosomal multivesicular bodies (exosomes) or the plasma membrane (microvesicles). Exosomes have a size around 50-200 nm, microvesicles range from around 150 to 1000 nm (6)(7)(8)(9)(10). EVs express also a number of surface markers, among those tetraspanins CD9, 63, and 81 are probably the most known.…”
Section: Introductionmentioning
confidence: 99%
“…This allows the identification of potential diagnostic and therapeutic markers in a non-invasive and costeffective way. For these reasons, EVs have been studied a lot in recent years (10,(16)(17)(18) and are an option worthy of being investigated to find new biomarkers of prognosis and prediction of sensitivity or resistance to therapy. In a recent study, we analyzed the circulating tumor cells in a patient with MpBC, discovering chromosomal alterations that may have a role in the metastatic cascade (19).…”
Section: Introductionmentioning
confidence: 99%